ESTIMATES OF THE SEVERITY OF COVID-19: A COMPARISON OF PAKISTAN WITH OTHER DEVELOPED COUNTRIES - Yasir Mehmood; Zafar Latif Awan; Adnan Afzal; Muhammad Saleem Akhtar; Fawad Hussain; Muhammad Imran Ashraf (Journal of University Medical & Dental College, 2020)
The number of confirmed cases of COVID-affected patients are 1,123,000 and counting while more than 59,000 corroborated mortalities have occurred around the globe, as depicted by the data gathered through Johns Hopkins University. More than 228,000 people have reportedly recovered from COVID-19 till April 4 2020. Italy has the second highest deaths of COVID-19 in the world. There is dire need to evaluate the pattern of COVID-19 in Pakistan and compared with other developed countries. World Health Organization has developed website to provide latest data in form of new reported cases, mortality and recoveries.  In Pakistan, mortality rate was found less than other developed countries and this hypothesis may be wrong that Pakistan neither will nor effected with virus due to climate conditions.The presented study had two objectives. The first was to describe the latest situation if COVID-19 in Pakistan and other developed countries. Second objective was to determine the latest situation about mortility rate in Pakistan and other developed countries. Comparative data was sketched and presented in the form of graph for 5 countries including Pakistan. All the data was obtained form WHO websites and from Pakistan government officials websites. Data was collected from Jan-2020 to 4 April-2020.